Preliminary landscape mapping and analys of ecological features of the island of Vaigach - A M Aleynikova (RUDN Journal of Ecology and Life Safety, 2013)
Selected on the basis of decoding of space pictures and analysis of the published data of natural-territorial complexes provide a first idea of the uniqueness of the landscape of the island of Vaigach. Climate warming will cause first of all the activity of the cryogenic and solifluctiv processes, increase horizontal inhomogeneity of the vegetation cover.